Toward dental caries: Exploring nanoparticle-based platforms and calcium phosphate compounds for dental restorative materials - Balhaddad, Abdulrahman A. (Bioact Mater, 2018)
Millions of people worldwide suffer from a toothache due to tooth cavity, and often permanent tooth loss. Dental caries, also known as tooth decay, is a biofilm-dependent infectious disease that damages teeth by minerals loss and presents a high incidence of clinical restorative polymeric fillings (tooth colored fillings). Until now, restorative polymeric fillings present no bioactivity. The complexity of oral biofilms contributes to the difficulty in developing effective novel dental materials. Nanotechnology has been explored in the development of bioactive dental materials to reduce or modulate the activities of caries-related bacteria. Nano-structured platforms based on calcium phosphate and metallic particles have advanced to impart an anti-caries potential to restorative materials. The bioactivity of these platforms induces prevention of mineral loss of the hard tooth structure and antibacterial activities against caries-related pathogens. It has been suggested that this bioactivity could minimize the incidence of caries around restorations (CARS) and increase the longevity of such filling materials. The last few years witnessed growing numbers of studies on the preparation evaluations of these novel materials. Herein, the caries disease process and the role of pathogenic caries-related biofilm, the increasing incidence of CARS, and the recent efforts employed for incorporation of bioactive nanoparticles in restorative polymer materials as useful strategies for prevention and management of caries-related-bacteria are discussed. We highlight the status of the most advanced and widely explored interaction of nanoparticle-based platforms and calcium phosphate compounds with an eye toward translating the potential of these approaches to the dental clinical reality.